2011
DOI: 10.1007/s00464-011-1624-2
|View full text |Cite
|
Sign up to set email alerts
|

Seprafilm slurry does not increase complication rates after laparoscopic colectomy

Abstract: The initial data regarding Seprafilm slurry indicate no significant difference in complication rates between the control and experimental groups. This is the first study to evaluate the safety of Seprafilm slurry for patients undergoing laparoscopic colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…As a solid sheet, Seprafilm is neither readily placed in the abdomen through laparoscopic incisions or trocar sites nor easily applied in small or confined anatomical locations. 12,13 Interestingly, some surgeons have reported the modification of Seprafilm by hydrating the film before surgical application, creating a "slurry" of modified HA/CMC. 14 Greenawalt and colleagues showed that this preparation was equally efficacious at reducing adhesion formation in animal models when compared to sheets of Seprafilm, but also had limited remote efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…As a solid sheet, Seprafilm is neither readily placed in the abdomen through laparoscopic incisions or trocar sites nor easily applied in small or confined anatomical locations. 12,13 Interestingly, some surgeons have reported the modification of Seprafilm by hydrating the film before surgical application, creating a "slurry" of modified HA/CMC. 14 Greenawalt and colleagues showed that this preparation was equally efficacious at reducing adhesion formation in animal models when compared to sheets of Seprafilm, but also had limited remote efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin was formed by the manufacturer's instructions from equal parts fibrinogen (75–115 mg/mL) and thrombin (500 IU/mL) for a total volume of 10 µL contained within each conduit. The HA/CMC was prepared as described previously: a 2 cm 2 sheet of Seprafilm was dissolved in 345 μL of warm saline (∼0.027 g/mL). A volume of ∼10 µL was placed inside each conduit using this HA/CMC slurry.…”
Section: Methodsmentioning
confidence: 99%
“…Η αποτελεσματικότητα και ασφάλεια του HA/CMC ως αντισυμφυτικό έχει φανεί σε πληθώρα πειραματικών εργασιών στις οποίες συμπεριλαμβάνονται μελέτες στις οποίες έχει δοκιμαστεί σε αναστομώσεις λεπτού και παχέος εντέρου [206][207][208][209][210][211][212][213][214]. Επίσης τουλάχιστον 9 τυχαιοποιημένες κλινικές μελέτες και πληθώρα από προοπτικές κλινικές μελέτες που επιβεβαιώνουν τα θετικά αποτελέσματα των πειραματικών εργασιών [215][216][217][218][219][220][221][222][223][224][225][226][227][228]. Όμως, παρόλο που το HA/CMC μειώνει σημαντικά το σχηματισμό μετεγχειρητικών συμφύσεων, δεν υπάρχουν στοιχεία από προοπτικές κλινικές μελέτες ότι επιφέρει μείωση της συχνότητας μετεγχειρητικού συμφυτικού ειλεού ούτε ότι αυξάνει τα ποσοστά επιτυχούς σύλληψης σε γυναίκες μετά από επεμβάσεις στην ελάσσονα πύελο [216].…”
Section: 65α μεμβράνη Yαλουρονικού Nατρίου / Kαρβοξυμεθυλοκυτταρίνης (Ha/cmc)unclassified
“…Όμως, παρόλο που το HA/CMC μειώνει σημαντικά το σχηματισμό μετεγχειρητικών συμφύσεων, δεν υπάρχουν στοιχεία από προοπτικές κλινικές μελέτες ότι επιφέρει μείωση της συχνότητας μετεγχειρητικού συμφυτικού ειλεού ούτε ότι αυξάνει τα ποσοστά επιτυχούς σύλληψης σε γυναίκες μετά από επεμβάσεις στην ελάσσονα πύελο [216]. Η εύθρυπτη και άκαμπτη υφή της μεμβράνης δυσχεραίνει την τοποθέτησή της σε λαπαροσκοπικά χειρουργεία, αλλά έχουν περιγραφεί μέθοδοι που υπερνικούν αυτό το τεχνικό πρόβλημα [219,229]. Υπάρχει, όμως, ανησυχία σχετικά με τη χρήση του σε χειρουργεία όπου πραγματοποιούνται αναστομώσεις πεπτικού.…”
Section: 65α μεμβράνη Yαλουρονικού Nατρίου / Kαρβοξυμεθυλοκυτταρίνης (Ha/cmc)unclassified